Human resource management demystified - DelCampo, Robert G. (New York McGraw-Hill, 2011)
The low-labor guide to mastering HRM! Want to dive into human resources but your brain says, "Help wanted!"? No problem! Put Human Resource. Management DeMYSTiFieD on the job, and you'll solve your dilemma in no time! Using a clear, step-by-step format, this practical guide provides a firm foundation in the basics of the field. You'll master all the key issues in human resources, like benefits, legal situations, hiring, training, outplacement, worker rights, and more. Detailed examples and concise explanations make it easy to grasp the material, and end-of-chapter quizzes and a final exam help reinforce learning. In no time, you'll build a firm foundation on the essential concepts and techniques instrumental to the success of any organization! This fast and easy guide features: Tips on designing and implementing a hiring plan; Tactics for developing and training new employees; Strategies for writing job descriptions, recruiting applicants, and selecting employees; Techniques for creating an effective compensation and benefits structure; Simple enough for a beginner, but challenging enough for an advanced student, Human Resource Management DeMYSTiFieD has everything you need to build a solid foundation in human resources.
Introduction -- Part 1: Overview And Compliance -- HR in a nutshell -- -- Functions of management -- HR: human resources or human relations? -- Challenges to HR -- Selecting HR strategies -- Equal Employment Opportunity (EEO) and the law -- Understanding the legal environment -- Ideal behavior and affirmative action -- Discrimination -- Antidiscrimination legislation -- Type of discrimination -- Equal Employment Opportunity Commission (EEOC) -- Definition of harassment -- Addressing EEO complaints -- Resources for further information -- Diversity in organizations -- What is diversity? -- Why manage employee diversity? -- Challenges in managing employee diversity -- Diversity in organizations -- Improving the management of diversity -- Part 2: Hiring for needs -- Job analysis -- Strategy and organizational structure -- Designing the organization -- Designing jobs and conducting a job analysis -- Job descriptions -- Special cases -- Employee selection -- Forecasting needs for employees -- Hiring process -- Issues in recruiting -- Issues in employee selection -- Part 3: They're hired-now what? -- Compensation -- Compensation -- Designing a compensation system -- Compensation tools -- Legal environment and pay system governance -- Benefits -- Overview of benefits -- Basic terminology -- Cost of benefits in the United States -- Types of benefits -- Benefits strategy -- Benefits mix -- Legally required benefits -- Voluntary benefits -- Administering benefits -- Training and development -- Training -- Training process -- Orientation and socialization -- Development -- Creating an effective development program -- Performance management and appraisal -- Performance management and appraisal basics -- Identifying performance -- Challenges in performance management -- Managing performance -- Pay for performance -- Types of pay-for-performance plans -- Employee rights and workplace safety -- Roles of the manager and the employee relations specialist -- Developing employee communications -- Types of information -- How communication works -- Encouraging effective communication -- Employee rights -- Management rights -- Employment at will -- Employee rights challenges: a balancing act -- Workplace safety and the law -- Managing contemporary safety, health, and behavioral issues -- Safety and health programs -- Employee discipline and responsibilities -- Disciplining employees -- Administering and managing discipline -- Basic standards of discipline -- Managing difficult employees -- Preventing the need for discipline with human resource management -- Employee separation, downsizing, and out placement -- Employee turnover -- Types of employee separations -- Layoffs -- Implementing a layoff -- Outplacement -- Working with organized labor -- Origins of US labor unions -- Labor relations -- Labor relations around the globe -- Labor relations strategy -- Managing labor relations -- HRM and union employees -- Index.
Includes index.
Keywords: Personnel management